Clarification of some imperfectly understood characters in the Chinese species Thalictrum przewalskii (Ranunculaceae), with reduction of T. lasiogynum and T. latistylum to its synonymy - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2021)
Based on critical observations on both herbarium specimens (including type material) and living plants in the wild, here we clarify some morphological characters in the Chinese species Thalictrum przewalskii (Ranunculaceae) and demonstrate that T. lasiogynum and T. latistylum, described respectively from China’s Sichuan and Gansu provinces, are conspecific with it. We therefore reduce T. lasiogynum and T. latistylum to the synonymy of T. przewalskii. Thalictrum sect. Platystylus, which was established to accommodate T. latistylum, is reduced to the synonymy under T. sect. Omalophysa. The identity of T. rockii is further confirmed and the distribution in China of T. sparsiflorum, a species most closely similar to T. przewalskii and widely distributed in northeastern Asia and North America, is also determined.